Combining ability analysis and gene action for some characters of pea (Pisum sativumL.) genotypes - Abdulla, Suaad Muhammad Sheikh (Sulaimani Journal for Pure and Applied Sciences, 2018)
Seven pea varieties Pisumsativum were sown in half diallel cross excluding reciprocals at winter season of 2013-2014 at Qliasan research station. During the winter season of 2014-2015, 28 genotypes (21 crosses + 7 parents) were sown in completely Randomized block design (CRBD), with three replications at Qliasan research station. The analysis of variance confirmed that the mean squares due to genotypes were highly significant for the characters secondary branches, fresh stem weight, dry stem weight and dry root weight, but it is significant for primary branches, fresh leaf weight and fresh root weight. The mean squares due to GCA and SCA were highly significant for most characters. The cross 4×5 showed maximum value for most characters. The crosses 3×4, 3×6 and 4×5 showed maximum heterosis values for the studied characters. Maximum positive GCA effect values produced by the parents 4, 5 and 6 for most characters, while maximum SCA effect values produced by the cross 4×5 for most characters. The ratio of σ2gca/σ2sca was less than unity for all characters. Average degrees of dominance due to all characters were more than unity, revealing the importance of non-additive gene effect in controlling the inheritance of these characters.
Keywords: Cowpea Genotypes; Grain yield; Correlation Analysis; Path Coefficient Analysis and Cluster Analysis